The impact of adenotonsillectomy on pediatric asthma. Issue 1 (29th November 2018) - Goldstein, Nira A.; Thomas, Maxwell S.; Yu, Yasong; Weaver, Diana E.; Watanabe, Izumi; Dimopoulos, Antonios; Wasserman, Jason; Ahmad, Sabina Q.; Ednick, Mathew; Vastola, A. Paul; Weedon, Jeremy
Abstract: Objective: To determine asthma outcomes in children undergoing adenotonsillectomy (T&A) for treatment of sleep‐disordered breathing (SDB). Hypothesis: Asthmatic children will demonstrate improvement in asthma control after T&A compared to asthmatic children not undergoing surgical treatment. Study Design: Prospective cohort. Patient‐Subject Selection: 80 children with diagnosed asthma, aged 4‐11, undergoing T&A and 62 controls matched to the T&A subjects by age, sex, and asthma severity classification. Methodology: Parents and children completed the Childhood Asthma Control Test (C‐ACT) and the Pediatric Sleep Questionnaire (PSQ). Parents were queried regarding the number of asthma exacerbations, the frequency of the use of systemic steroids, the number of emergency room visits and the number of hospitalizations in the prior 6 months. The identical questionnaires and interviews were completed 6 months after entry. Results: The adjusted mean (95% CI) C‐ACT score was 21.86 (20.94‐22.68) at entry and 25.15 (24.55‐25.71) at follow‐up for the T&A group compared with 22.42 (21.46‐23.28) and 23.59 (22.77‐24.33) for the control group. There was a significant group by time interaction ( P  < 0.001). Simple effects analysis showed that group means did not differ at entry ( P  = 1.00) but did differ at follow‐up ( P  = 0.006). Baseline PSQ was a significant predictor of improvement in C‐ACT scores. Statistical modeling did not demonstrate significant group by time interactions for any of the asthma clinical outcomes, although these outcomes were very infrequent in both groups. Conclusion: Treatment of SDB improves asthma outcomes as measured by the C‐ACT.